Impact of Body Temperature in Patients With Acute Basilar Artery Occlusion: Analysis of the BASILAR Database - Zhang, Wenbin; Li, Fengli; Zhang, Cai; Lei, Bo; Deng, Wei; Zeng, Hongliang; Yu, Yang; Wu, Junxiong; Peng, Daizhou; Tian, Zhenxuan; Zhu, Xiurong; Hu, Zhizhou; et al. (Frontiers in Neurology, 2022)
Background A link between body temperature and stroke outcomes has been established but not for acute basilar artery occlusion. We aimed to determine the association between body temperature and clinical outcomes in patients with acute basilar artery occlusion and temperature management range. Methods We included patients from the Endovascular Treatment for Acute Basilar Artery Occlusion Study (BASILAR) database with records of both admission body temperature (ABT) and peak body temperature (PBT). ABT was defined as the body temperature first measured at the hospital visit, PBT was defined as the highest temperature within 24 h of treatment, and minus body temperature (MBT) was defined as PBT-ABT. The primary clinical outcome was favorable functional outcome, defined as the proportion of patients with a modified Rankin Scale score of 0–3 at 3 months. Secondary outcomes included 3-month mortality, in-hospital mortality, and symptomatic cerebral hemorrhage. Results A total of 664 patients were enrolled in the study; 74.7% were men, with a median age of 65 (interquartile range, 57.25–74) years. In all patients, multivariate analysis indicated that PBT and MBT were independent predictors of favorable functional outcome [odds ratio (OR), 0.57 (95% CI, 0.43–0.77); OR, 0.68 (95% CI, 0.52–0.88), respectively], and higher ABT, PBT, and MBT were associated with an increased 3-month mortality [OR, 1.47 (95% CI, 1.03–2.10), OR, 1.58 (95% CI, 1.28–1.96), OR, 1.35 (95% CI, 1.11–1.65), respectively]. Proportional odds models demonstrated that when ABT, PBT, MBT were in the range of <37.5, <38.9, and −0.6–2.7°C, respectively, the benefit of the endovascular treatment is clearly greater than that of standard medical treatment in terms of favorable functional outcome. Conclusions Body temperature is an independent predictor of clinical outcome in patients with acute basilar artery occlusion. It is necessary to control the patient body temperature within the appropriate range in clinical settings. Trial Registration Chinese Clinical Trial Registry ChiCTR1800014759. Registered 03 February 2018. Retrospectively registered.